Sustainability of Alternative Energy for Organic Rankine Cycle Power Plant in Thailand - Chaiyat, Nattaporn (Naresuan University Journal: Science and Technology (NUJST); Vol 23 No 1 (2015): January-April 2015, 2015)
This paper studies the possibility of power generation by using alternative energy in Thailand, which are geothermal energy, solar energy and waste energy based on the energy, economic and environment indicators. An Organic Rankine Cycle (ORC) is used to generate electricity from heat sources of hot springs, solar water heating system and RDF-5, respectively. In this study, a 20 kW e ORC system with using R-245fa as working fluid was tested and evaluated the system efficiency. From the testing results, it could be found that the efficiency of ORC system was around 8%, when hot water temperature was higher than 100 °C. From simulation results, the values of electricity costs (EC) of geothermal energy, solar energy and waste energy are 0.166, 0.747 and 1.037 USD/kWh, respectively. For environmental impact, the carbon dioxide intensity per net electricity output of geothermal, solar and waste power plants are 0.186, 0.537 and 2.380 kg CO 2 /kWh, respectively. The suitable alternative energy for generating electricity is geothermal energy, which is beneficial than the solar and waste energy power plants based on the energy, environment and economic results. Free operating cost is the main factor, which supports that the geothermal power plant is the suitable technique. Keywords : Organic Rankine Cycle, Geothermal Energy, Solar Energy, Waste Energy, Electricity Costs
Keywords: Organic Rankine Cycle, Geothermal Energy, Solar Energy, Waste Energy, Electricity Costs